Physiology of a female junior world cross-country cycling champion: From youth categories to junior success - Fornasiero, A.; Savoldelli, A.; Modena, R.; Pellegrini, B.; Schena, F. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Cross-country bikers require highly developed aerobic and anaerobic systems to sustain performance demands [1]. Although these physiological characteristics, as well as a specific anthropometry, seem to be a prerequisite to compete successfully in adult age, few data are available about the development of these characteristics. This study shows the evolution of a young female cyclist, from youth categories to her success as junior world champion. Methods: Every year during the competition period, from 14 to 16 years old, the athlete underwent an anthropometric evaluation, an incremental test and a 30 s Wingate Test. Throughout this period she competed for the national youth team. This has permitted a comparison with same age female bikers performing equal assessments. Results: Height and body mass grew from 159.7 cm; 50.1 kg at 14 years old to 161.2 cm; 53.7 kg at 16 yo. VO2peak was 3.49 L/min at 14 yo, showing the highest relative value: 70 ml/kg/min. VO2peak increased at 3.68 L/min at 16 yo. PPO and PRCP increased from 14 to 16 yo, reaching at 16 yo 362 W (6.7 W/kg) and 282 W (5.3 W/kg) respectively. Peak anaerobic power increased from 710 W (14.2 W/kg) to 844 W (15.7 W/kg). Discussion: Anthropometric evolution defined a morphological profile advantageous for cross-country performance, where a weight-optimization is required [1]. In each session VO2peak was the highest seen within the youth national team, +18% ( 0.5 L/min) at 14 yo, +10% ( 0.35 L/min) at 16 yo, and even exceeded values reported in top level bikers [2]. Also PPO and PRCP were higher than those reported in literature [2]. At 16 yo anaerobic indices showed the highest differences compared with same age national athletes with +19% in Pmax production (W/kg), with values greater than those of 4 female professional cyclists (12°-86° ranking UCI). Conclusion: The characteristics required to compete successfully in cross-country cycling [2] are already highly developed in a young female junior world champion. At 16 years old, before entering in junior category, winning a world title, the athlete showed physiological values comparable to top class bikers, producing high power-to-weight ratios and high anaerobic power peaks.